Reel time : movie exhibitors and movie audiences in prairie Canada, 1896 to 1986 - Seiler, R. M. (Robert Morris) (AU Press, 2013)
In this authoritative work, Seiler and Seiler argues that the establishment and development of moviegoing and movie exhibition in Prairie Canada is best understood in the context of changing late-nineteenth-century and early-twentieth-century social, economic, and technological developments. From the first entrepreneurs who attempted to lure customers in to movie exhibition halls, to the digital revolution and its impact on moviegoing, Reel Time highlights the pivotal role of amusement venues in shaping the leisure activities of working- and middle-class people across North America. As marketi.